Pelatihan Pembuatan Modul Ajar Berbasis Proyek untuk Guru dalam Implementasi Kurikulum Merdeka Belajar di SD N wasur 2 - Ginting, Syahfitriani Br; Kaize, Bernadetha Rizki; Diliana, Ekfindar (Journal Of Human And Education (JAHE), 2025)
Teachers' understanding in making project-based teaching modules is still less than optimal in the implementation of the independent learning curriculum. This service aims to improve the ability of teachers at SD N Wasur 2 to create project-based teaching modules in the implementation of the Merdeka curriculum. This activity was carried out through training and mentoring, involving 20 teachers as participants in the training activities. The evaluation was carried out using Pretest to measure the teacher's initial ability and Posttest to measure the teacher's final ability in training activities. From the training activities, questions were given in the form of multiple-choice questions as many as 30 questions. Data analysis was carried out using Gain score to find out the difference between the initial and final abilities of the trainees. The results of the activity showed that the increase was 0,55 in the medium category. Training activities have a positive influence on improving teachers' ability to create project-based teaching modules in the implementation of the Merdeka curriculum. The teachers hope to get similar activities carried out to support the continuous improvement of teachers' knowledge and professionalism.